2017
DOI: 10.11604/pamj.2017.28.260.10463
|View full text |Cite
|
Sign up to set email alerts
|

Séroprévalence de la cysticercose et facteurs de risque associés chez un groupe de patients vus au Centre Hospitalier Régional de Référence d’Antsirabe, Madagascar

Abstract: IntroductionA Madagascar, la cysticercose, maladie causée par la forme larvaire de Taenia solium, demeure un problème de santé publique. En 2003, la séroprévalence de la cysticercose variait entre 7% et 21% avec un taux plus élevé dans les régions centrales de l’île. Toutefois, depuis une dizaine d’année, les données épidémiologiques concernant la cysticercose humaine restent limitées. Notre étude a pour objectif de déterminer, chez les patients issus de la région de Vakinankaratra et qui sont suspects cliniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Consumption of pork is important in the transmission of Taenia solium infections. Its prevalence is higher among consumers of pork compared to those who do not eat [29]. In our study, a patient contracted neurocysticercosis through the practice of geophagy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Consumption of pork is important in the transmission of Taenia solium infections. Its prevalence is higher among consumers of pork compared to those who do not eat [29]. In our study, a patient contracted neurocysticercosis through the practice of geophagy.…”
Section: Discussionmentioning
confidence: 57%
“…We noted that 84.6% of the patients had contact with pigs (consumers, breeders and sellers). Za indraide, et al [29] found 96.6% of consumers of pork, 39% of whom were breeders. Some studies have shown the link between cysticercal prevalence and the intensity of pig farming [30].…”
Section: Discussionmentioning
confidence: 96%
“…A serological survey of human cysticercosis including 4,375 samples between 1994-1999, using an ELISA test for screening and EITB (Enzyme-linked Immunoelectro Transfer Blot) for confirmation, showed a prevalence varying from 7 to 21% in the different provinces [10]. In 2013, a cysticercosis survey at the Antsirabe Hospital (Vakinankaratra region) using a commercial Western Blot (LD Bio Diagnostic, Lyon, France) revealed 14.7% seropositivity (35 positives out of 237) [11].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Taenia solium is endemic in Madagascar, where it has been reported since 1901 (Migliani et al ., 2000 ; Carod and Dorny, 2020 ). Neurocysticercosis is widespread in Madagascar (Andriantsimahavandy et al ., 2003 ), with infection levels in school-aged children a particular concern (Zafindraibe et al ., 2017 ; Carod et al ., 2021 ). It is the main cause of secondary childhood epilepsy (Carod and Dorny, 2020 ) and a major cause of late-onset epilepsy (Andriantsimahavandy et al ., 1997 ) in Madagascar.…”
Section: Introductionmentioning
confidence: 99%